Strengthening Legal Certainty on the Electronic Registration System of Fiduciary Deed in Indonesia - Maria Pranatia (Universitas Pelita Harapan, 2021)
Fiduciary guarantee constitute a type of guarantee commonly used by the business society to obtain loan from Banks or other financial institutions. Administratively, since the government established an electronic fiduciary registration system, the system has in fact, not been fully supported by appropriate legal grounds. This research aims to explore and analyze regulations regarding the legal status of fiduciary agreements along with its electronic registration system and the role of Notary Public with the aim of providing recommendation to the ideal registration system supported by proper laws and regulations. Methodology of this study is based on normative legal research which carried out several approaches such as statutory approach, comparative approach and conseptual approach. The results of the study essentially emphazied the need for amandement and harmonization of Law No. 45/1999 concerning Fiduciary Guarantee as well as its implementing regulations. Ultimately, the Indonesia fiduciary guarantee and its registration system will always in harmony with the values of legal certainty, justice and usefulness.